Evaluation of physicochemical properties and in-vitro release profile of glipizide-matrix patch - Kajal Ghosal; Rajan Rajabalaya; Anindya Kishore Maiti; Bikramaditya Chowdhury; Arunabha Nanda (Universidade de São Paulo, 2010)
OBJECTIVES: The aim of the present investigation was to form matrix patches with ethyl cellulose (EC) as the base polymer, polyvinyl pyrrolidone (PVP) as the copolymer, plasticizer with dibutyl phthalate (DBP) or acetyl tributyl citrate (ATBC) and the drug glipizide (gz) by the solvent casting method. Physicochemical properties of the patches and in vitro drug release were determined in a modified Keshary-chien diffusion cell to optimize the patch formulations with the help of experimental data and figures for further studies. TECHNIQUES: EC and PVP of different proportions with different weight percentages of either DBP or ATBC and a fixed amount of glipizide were taken for matrix patch formations. The dried patches were used for measuring their drug contents as well as their thicknesses, tensile strengths, moisture contents and water absorption amounts in percentage. In vitro release amounts at different intervals were measured by UV-spectrophotometer. RESULTS: Drug contents varied from 96 - 99%. Thickness and tensile strength varied due to weight variation of the ingredients in the matrix patches. Moisture content and water absorption in wt % were greater for the patches containing higher amount of PVP due to its hydrophilic nature. Variations in drug release were observed among various formulations. It was found that all of the releases followed diffusion controlled zero order kinetics. Two DBP patches yielded better and more adequate release. CONCLUSIONS: The two formulations with DBP were the preferred choice for making matrix patches for further studies. O objetivo da presente pesquisa foi formar matrizes para bandagens de liberação transdérmica com etilcelulose (EC) como polímero base, polivinilpirrolidona (PVP), como copolímero, plastificante com ftalato de dibutila (DBP) ou citrato de tributilacetila (ATBC) e o fármaco glipizida (gz) pelo método de evaporação do solvente (moldagem com solvente). As propriedades físico-químicas das bandagens e a liberação do fármaco in vitro na célula de difusão de Keshary-chien modificada foram determinadas para aperfeiçoar as formulações das bandagens com o auxílio de dados experimentais e figuras para estudos posteriores. EC e PVP em diferentes proporções com porcentagens diferentes de massa tanto de DBP quanto de ATBC e quantidade fixa de glipizida foram utilizadas como matrizes para a formação de bandagens de liberação transdérmica. As bandagens secas foram empregadas para medir seus conteúdos em fármaco e, também, a sua espessura, resistência à tensão, conteúdos de umidade e porcentagem de absorção de água. As quantidades liberadas in vitro em diferentes intervalos de tempo foram medidas por espectrofotômetro de UV. Os conteúdos de fármaco variaram de 96 a 99%. A espessura e a resistência à ruptura variaram devido à variação de massa dos componentes da matriz das bandagens. O conteúdo de umidade e a água absorvida, em porcentagem de massa, foram maiores para as bandagens que continham grandes quantidades de PVP devido à sua natureza hidrofílica. As variações na liberação de fármaco foram observadas entre as várias formulações. Todas as liberações seguiram a cinética de difusão controlada de ordem zero. Duas bandagens DBP resultaram em melhor e mais adequada liberação. As duas formulações com DBP foram escolhidas para a preparação de matriz de bandagens para estudos posteriores.